Factors Influencing Public Intention to Use the Kepahiang Local Tax Mobile Application: An Adapted UTAUT Perspective - Escobar, Franco; Tjhin, Viany Utami (Indonesian Scientific Journal, 2025)
This study aims to identify factors that influence the public’s behavioral intention to use the Kepahiang Local Tax Mobile Application. Developed by the Regional Government of Kepahiang Regency through the Revenue Division of the Regional Financial Agency, the application facilitates local tax payments, particularly for PBB-P2 (Rural and Urban Land and Building Tax). The research adopts an extended Unified Theory of Acceptance and Use of Technology (UTAUT) framework, incorporating additional variables such as Computer Self-Efficacy and Cost of Service, along with original UTAUT constructs: Performance Expectancy, Effort Expectancy, Social Influence, and Facilitating Conditions. It also examines moderating variables including Gender, Age, and Experience. Data were gathered through a questionnaire distributed to 152 respondents and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results reveal that Performance Expectancy and Social Influence significantly and positively affect Behavioral Intention to use the application, whereas Cost of Service shows a negative influence. Furthermore, Gender is found to moderate the relationship between Social Influence and Behavioral Intention. These findings offer insights into the key factors influencing the adoption of government mobile applications, serving as a useful reference for policymakers aiming to increase user acceptance and enhance the effectiveness of digital public services.